2013
DOI: 10.1523/jneurosci.4703-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Gata3 Is a Critical Regulator of Cochlear Wiring

Abstract: Spiral ganglion neurons (SGNs) play a key role in hearing by rapidly and faithfully transmitting signals from the cochlea to the brain. Identification of the transcriptional networks that ensure the proper specification and wiring of SGNs during development will lay the foundation for efforts to rewire a damaged cochlea. Here, we show that the transcription factor Gata3, which is expressed in SGNs throughout their development, is essential for formation of the intricately patterned connections in the cochlea. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
100
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(113 citation statements)
references
References 49 publications
(80 reference statements)
8
100
1
4
Order By: Relevance
“…However, little is known about the cues that regulate these early wiring events, though several neurotrophins, classical guidance molecules, and extracellular matrix proteins are clearly involved (Appler et al, 2011; Coate et al, 2013; Defourny et al, 2011; Yang et al, 2011a). In addition, intrinsic factors act in SGNs to influence these wiring events, with the transcription factor Gata3 playing a major role in the initiation and coordination of SGN differentiation (Appler et al, 2013; Duncan et al, 2013; Luo et al, 2013) and Prox1 ensuring that Type II SGN fibers are oriented toward the base of the cochlea (Fritzsch et al, 2010). Indeed, Type II afferents can be recognized as early as E16.5, based on their morphology, consistent with the idea that these initial guidance events are intrinsically controlled (Koundakjian et al, 2007).…”
Section: Development Of the Auditory Ribbon Synapsementioning
confidence: 99%
“…However, little is known about the cues that regulate these early wiring events, though several neurotrophins, classical guidance molecules, and extracellular matrix proteins are clearly involved (Appler et al, 2011; Coate et al, 2013; Defourny et al, 2011; Yang et al, 2011a). In addition, intrinsic factors act in SGNs to influence these wiring events, with the transcription factor Gata3 playing a major role in the initiation and coordination of SGN differentiation (Appler et al, 2013; Duncan et al, 2013; Luo et al, 2013) and Prox1 ensuring that Type II SGN fibers are oriented toward the base of the cochlea (Fritzsch et al, 2010). Indeed, Type II afferents can be recognized as early as E16.5, based on their morphology, consistent with the idea that these initial guidance events are intrinsically controlled (Koundakjian et al, 2007).…”
Section: Development Of the Auditory Ribbon Synapsementioning
confidence: 99%
“…GATA3 belongs to the GATA family of zinc finger transcription factors, which are named according to their DNA binding sequence (GATA). GATA3 plays an important role in inner ear development [2-4], and mutations affecting GATA3 are associated with HDR syndrome, which stands for hypoparathyroidism, deafness, and renal dysplasia [5-22]. It has been reported that patients with GATA3 mutations present with early-onset sensorineural hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, neurogenesis initiates as CVG neuronal progenitors emanate from the otic placode at E9.5 and finishes at E15.5 to form the CVG, which later separates into the spiral and vestibular ganglia (Fritzsch et al, 2002; Fritzsch et al, 1999; Morsli et al, 1998). Studies have implicated the essential roles of several transcription factor genes in the development of CVG neurons, such as the bHLH genes Neurog1 (Ma et al, 1998) and Neurod1 (Kim et al, 2001; Liu et al, 2000) , and the GATA family gene Gata3 (Appler et al, 2013; Duncan and Fritzsch, 2013; Duncan et al, 2011; Economou et al, 2013; Jones and Warchol, 2009; Lawoko-Kerali et al, 2002; Lawoko-Kerali et al, 2004; Luo et al, 2013). …”
mentioning
confidence: 99%